The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1590/s0004-28032002000100010
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos dos efeitos do sono no aparelho digestório

Abstract: RESUMO -Racional -Durante o sono ocorrem modificações no funcionamento do aparelho digestório decorrentes da diminuição da influência do sistema nervoso central. Embora haja resultados controversos, decorrentes das dificuldades metodológicas de estudo do aparelho digestório durante o sono, no geral, a atividade está diminuída. A função do aparelho digestório sofre influência do meio ambiente e de estímulos recebidos pelo ser humano. O estado de sono ou vigília faz com que a influência do meio externo seja melh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Gastric emptying is slow during sleep, but rapid eye movement (REM) sleep is associated with faster gastric emptying. 24 Children who take "afternoon naps" reach REM sleep faster after sleep onset than preadolescents who have discontinued their afternoon naps. In preadolescents and adolescents, the REM sleep is dominantly in the last two-thirds of the night.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric emptying is slow during sleep, but rapid eye movement (REM) sleep is associated with faster gastric emptying. 24 Children who take "afternoon naps" reach REM sleep faster after sleep onset than preadolescents who have discontinued their afternoon naps. In preadolescents and adolescents, the REM sleep is dominantly in the last two-thirds of the night.…”
Section: Discussionmentioning
confidence: 99%
“…32 Another factor that could have influenced our findings is that increased gastric volume leads to greater physical discomfort and thus impairs the consolidation of sleep onset. It has been demonstrated that sleep decreases the activity of the digestive tract, 33 which may have an overloaded activity during the night if food intake is excessive.…”
Section: Anthropometric Evaluationmentioning
confidence: 99%
“…Total metformin exposure was lower with once-daily am dosing than with once-daily pm or twice-daily dosing. Slowed gastrointestinal transit during sleep [ 36 ] following pm dosing may allow prolonged metformin contact with gut transporters which modestly increases absorption relative to morning dosing. Indeed, the right-shifted PK profile with Metformin DR pm dosing compared with am dosing (together with previous findings that Metformin DR pm dosing results in peak concentrations approximately 10 h post-dose [ 5 ]) is probably responsible for the elevated am concentrations observed with Metformin DR vs Metformin IR observed in study 1.…”
Section: Discussionmentioning
confidence: 99%